Phenology of medicinal snake gourd (Trichosanthes cucumerina L.) under different seasons - Harsha Satheesh (Academy of Climate Change Education and Research, 2015)
The present study entitled “Phenology of medicinal snake gourd (Trichosanthes cucumerina L.) under different seasons” was carried out at Academy of Climate Change Education and Research (ACCER), Vellanikkara during the period 2014-2015. Field experiments were conducted at All India Coordinated Research Project on Medicinal, Aromatic Plants and Betel Vine (AICRP on MAP & B), College of Horticulture, Vellanikkara. The objective of the study was to assess the influence of weather parameters on yield and yield attributing characters of medicinal snake gourd (Trichosanthes cucumerina L.) under open and rain shelter during winter, summer and rainy seasons. The experiment was laid out in a randomized block design with six treatments and four replications each in open and rain shelter during winter, summer and rainy seasons. Observations on meteorological, growth characters, floral biology, yield and quality parameters were recorded under open and rain shelter in all the three seasons. Significant difference was observed in number of flowers, number of fruits produced, pollen fertility, fruit yield per plant, herbage yield per plant, total yield per plant and per plant cucurbitacin content for plants grown under rain shelter as well as in open condition during the three seasons. During winter, summer and rainy seasons crops grown under rain shelter recorded highest vine length, number of branches, maximum leaf area and number of male and female flowers produced, herbage yield per plant and dry yield per plant than open condition. Whereas pollen fertility, pollen viability and fruit weight were found to be highest in open condition than in rain shelter during summer season and found more in rain shelter during winter and rainy seasons. Earlier anthesis of both male and female flower was recorded during summer season under open condition. Highest herbage yield per plant, fruit yield per plant and total yield per plant were recorded under open condition during summer season. But during rainy season it is higher under rain shelter when compared to open field.Per plant cucurbitacin content was highest for the plants that grown under open environment than in rain shelter. It was found to be maximum during summer season followed by winter and rainy season. Weather parameters such as canopy air temperature, daily minimum and maximum temperature were high under rain shelter during the three cropping seasons. Relative humidity and soil moisture were high under rain shelter during winter and summer and low during rainy season. Correlation analysis with the weather parameters and crop was studied. Relative humidity and soil moisture had a significant negative correlation with the number of male flowers produced, pollen fertility, herbage yield per plant, total yield per plant and per plant cucurbitacin content. Canopy air temperature, minimum and maximum temperature showed positive correlation with the number of male flowers, produced pollen fertility, number of fruits, fruit yield per plant, herbage yield per plant, total yield per plant and per plant cucurbitacin content whereas rainfall had a negative correlation.